Reducing Accounting Complexity in Manufacturing MSMEs through Iterative Design of General Code-Based Systems - Adhitya Bayu Suryantara; Hudaya, Robith; Ridhawati, Rini; Pratama, Ade Yoga (Jati: Jurnal Akuntansi Terapan Indonesia, 2026)
Accounting complexity is one of the main factors behind MSMEs' resistance to preparing financial information. However, with technological advancements, lengthy, complex accounting cycles can be streamlined. This study aims to develop a web-based accounting system using a general code recognition method to automatically classify transaction activities into specific account types, assisting MSME owners in preparing financial reports, and reducing perceived accounting complexity by improving accessibility, usability, and informational value. The research involves alpha version system development, user workshops, system implementation among participant MSMEs, interviews to explore perceptions and experiences, and result interpretation. Findings show that of 12 beta testers, 7 consistently entered data over 4 consecutive months and found the system helpful; 3 found it helpful but struggled with consistency; and 2 were not interested. Nine MSMEs found the system’s information especially useful for understanding cash flow, inventory, and cost of goods sold. Meanwhile, six MSMEs have started using the system's financial ratios to manage business operations. This study contributes by providing a practical technological solution that simplifies accounting processes for MSMEs while offering insights into how web-based accounting systems can reduce perceived accounting complexity and improve the use of financial information for business decision-making.